Retooling Politics : How Digital Media Are Shaping Democracy - Jungherr, Andreas; Rivero, Gonzalo; Gayo-Avello, Daniel (Cambridge University Press, 2020)
Donald Trump, the Arab Spring, Brexit: digital media have provided political actors and citizens with new tools to engage in politics. These tools are now routinely used by activists, candidates, non-governmental organizations, and parties to inform, mobilize, and persuade people. But what are the effects of this retooling of politics? Do digital media empower the powerless or are they breaking democracy? Have these new tools and practices fundamentally changed politics or is their impact just a matter of degree? This clear-eyed guide steps back from hyperbolic hopes and fears to offer a balanced account of what aspects of politics are being shaped by digital media and what remains unchanged. The authors discuss data-driven politics, the flow and reach of political information, the effects of communication interventions through digital tools, their use by citizens in coordinating political action, and what their impact is on political organizations and on democracy at large.
Keywords: 320